Physical Characteristics of Substituted Biscuits with Bee Pollen - Anis, Ulfah; Fatharani, Arina; Yuwita, Fitri; Gusriani , Ika (Badan Penerbitan Fakultas Pertanian (BPFP), 2024)
Bee pollen is one of the popular bee products besides propolis and honey. It contains good nutrition for the body and has been used to boost nutrition as a fortification or substitution ingredient in various food preparations such as biscuits. This study aims to determine the effect of storage time on the physical characteristics of a substituted biscuit with bee pollen. The experimental design was a Completely Randomized Design (CRD) with one factor as the storage time of days 0, 2, 5, 7, 9, 12, 14, 16, and 19. The result showed that the storage time significantly influenced the texture and weight change of substituted biscuits with bee pollen while the water content was not significantly affected.